1995
DOI: 10.1073/pnas.92.25.11814
|View full text |Cite
|
Sign up to set email alerts
|

CD38 ligation induces tyrosine phosphorylation of Bruton tyrosine kinase and enhanced expression of interleukin 5-receptor alpha chain: synergistic effects with interleukin 5.

Abstract: Mouse CD38 has been implicated in the regulation of both B-cell proliferation and protection of B cells from irradiation-induced apoptosis. CD38 ligation on B cells by CS/2, an anti-mouse CD38 monoclonal antibody, induced proliferation, IgM secretion, and tyrosine phosphorylation of Bruton tyrosine kinase in B cells from wild-type mice. B CD38 is a type II transmembrane glycoprotein and is an ectoenzyme that possesses both ADP-ribosyl cyclase and cADP-ribosyl hydrolase activities, which generate cADPribose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
55
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 45 publications
4
55
0
Order By: Relevance
“…We have reported that CD38 ligation on B cells by anti-mouse CD38 mAb induced proliferation, IgM secretion, and tyrosine phosphorylation of Bruton tyrosine kinase (Btk) in B cells from wild-type mice. B cells from X chromosome-linked immunodeficient (Xid) mice did not respond at all to anti-CD38 mAb although CD38 expression on these B cells was comparable to that on wild-type B cells (8,9). We infer from these results that Btk activity is involved in B cell triggering after cross-linkage of CD38.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…We have reported that CD38 ligation on B cells by anti-mouse CD38 mAb induced proliferation, IgM secretion, and tyrosine phosphorylation of Bruton tyrosine kinase (Btk) in B cells from wild-type mice. B cells from X chromosome-linked immunodeficient (Xid) mice did not respond at all to anti-CD38 mAb although CD38 expression on these B cells was comparable to that on wild-type B cells (8,9). We infer from these results that Btk activity is involved in B cell triggering after cross-linkage of CD38.…”
mentioning
confidence: 87%
“…A role for CD38 in regulation of B cell activation has been suggested by analysis using agonistic mAb to mouse CD38 (5)(6)(7)(8)(9). We have reported that CD38 ligation on B cells by anti-mouse CD38 mAb induced proliferation, IgM secretion, and tyrosine phosphorylation of Bruton tyrosine kinase (Btk) in B cells from wild-type mice.…”
mentioning
confidence: 99%
See 3 more Smart Citations